Pertumbuhan Biji Teratai (Nymphaea pubescens Willd.) pada Kondisi Asam dan Lamanya Pencahayaan Alami - Chatimatun Nisa; B.N Ismuhajaroh (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Lotus is a water plant that thrives in the swamp waters of South Kalimantan. These plants in some areas are rapidly decreasing due to expansion, urbanization, industrialization, and other land uses that affect their habitat. The germination and growth of lotus seeds are very dependent on the state of the surrounding environment, especially the level of acidity and lighting from sunlight. This study aims to determine the effect of acidity and the duration of natural lighting on the growth of lotus seeds. The study was conducted at the Laboratory of Agricultural Biology, Faculty of Agriculture ULM from March to June 2016. The design used was a Separate Plot Design in a Randomized Block Design, as the main plot was the acidity level of water consisting of 11 levels and as a subplot was the lighting duration consisting of 5 levels with two replications. The results showed that lotus seeds can grow from media which have an acidity level (pH) 3-3.5 and a base pH of 7.5-8. Seeds can germinate and grow in both dark and bright conditions, but treatment with a long exposure time of 7 and 24 hours of light is the best.